Answer:
The zeros of the function:
![x=2,\:x=-4](https://img.qammunity.org/2022/formulas/mathematics/high-school/du440b9rgkjqqwpuqlmlhlgh79bcmdnnzn.png)
Explanation:
Given the function
![f\left(x\right)=x^2+2x-8](https://img.qammunity.org/2022/formulas/mathematics/high-school/9ek9inphaiw2vh25ipbqinqi03158lrhxq.png)
In order to determine the zeros of the function, substitute f(x) = 0
![x^2+2x-8\:=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/darm4okt3mojh28k57vknuafrwt7veg866.png)
Breaking the expression x²+2x-8=0 into groups
![\:\left(x^2-2x\right)+\left(4x-8\right)=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/z5rzketzrihubf3w4o5dn2v5gojw6q6jz6.png)
Factor out x from x²-2x: x(x-2)
Factor out 4 from 4x-8: 4(x-2)
so
![x\left(x-2\right)+4\left(x-2\right)=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/d84a35wvjjca2zkzu12sqvad2uaxhe4671.png)
Factor out common term: x-2
![\left(x-2\right)\left(x+4\right)=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/aq4o890dryvnay4mmuyuqksj183rh42xta.png)
Using the zero factor principle
if ab=0, then a=0 or b=0 (or both a=0 and b=0)
![x-2=0\quad \mathrm{or}\quad \:x+4=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/fxu5a41x4aykszzmkcck8ljrptzjbepr2r.png)
solving x+2 = 0
x+2 = 0
x = -2
solving x+4=0
x+4 = 0
x = -4
Therefore, the zeros of the function:
![x=2,\:x=-4](https://img.qammunity.org/2022/formulas/mathematics/high-school/du440b9rgkjqqwpuqlmlhlgh79bcmdnnzn.png)